Rating of Banks under Systemic Instability (Economics and region, 2019)
This article investigates the predictive ability of rating methodologies of banks based on scoring approach, financial ratios and open data on Ukrainian banks. As a result of the comparative analysis of rating indexes dynamics for groups of active and bankrupt banks during the system crisis and recovery 2014-2018, it was found that ratings based only on open data may have a high ability to bankruptcy early warning, because the final scores for the further defaulted banks were below the median values of the system. Moreover, insolvent banks were inclined to gradually lose their position in the rating for a few quarters before the default. The findings from the retrospective analysis were used to select the most significant default indicators for banks, which are the basis of the updated methodology based on newly disclosed data on a bank-by-bank basis.
Keywords: banking system; systemic risk; bank solvency rating; financial crisis; default